Comprehensive cytopathology - Bibbo, Marluce , 1939-; Wilbur, David C. (Elsevier, 2015)
In the newly updated edition of Comprehensive Cytopathology, a team of international experts provides criteria and techniques in diagnosis, testing, and new insights in cytology. This accessible guide to diagnostic investigation and screening is ideal for daily laboratory use, taking a systematic approach to helping you understand major diagnostic criteria as well as the pitfalls and limitations of cytology. Quickly find the answers you need through a consistent chapter structure. Realize every possibility. Appropriate histopathological correlations and a consideration of the possible differential diagnosis accompany the cytological findings.